The importance of the Utinga Camilo Viana State Park for the conservation of plant and fungal species in the metropolitan region of Belém, Pará, Brazil - Ferreira, Leandro Valle; Miranda, Adria da Silva; Gurgel, Ely Simone Cajueiro; Santos, João Ubiratan dos; Brito, Evellyn Garcia; Maia, Arnold Patrick de Mesquita (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
There are few botanical inventories in the conservational units of the metropolitan region of Belém, most limited to a few biological groups. In order to fill this gap, the Utinga Flora Project was created with the main objective of creating a reference collection of plant and fungus species of the vegetation types of the Utinga State Park. Samples were taken of all life forms in the aquatic and terrestrial habitats. In this study, 701 plant species distributed among 110 families and 16 fungal species. The most species-rich families were Fabaceae, Araceae, Orchidaceae, Melastomataceae, Rubiaceae and Bignoniaceae. The arboreal life form was represented by 46% of the species, followed of lianas, shrubs, herbs, epiphytes. totaling 49% of the species. This demonstrates the importance of these life forms that are neglected in inventories. In conclusion, the Utinga Flora Project demonstrates that the species richness of plant and fungal life is very considerable. These findings reveal the importance of collection efforts in increasing knowledge about the occurrence of species in the Amazon and demonstrate the relevance of the Park for the conservation of flora, that represent one of the last of native vegetation in one of the most deforested regions in the Amazon.